WITHDRAWN: Utilizing comparative models in biomedical research - Little, Alexander G.; Pamenter, Matthew E.; Sitaraman, Divya; Templeman, Nicole M.; Willmore, William G.; Hedrick, Michael S.; Moyes, Christopher D. (Comparative biochemistry and physiology. Part A, Molecular & integrative physiology, 2021)
The Publisher regrets that this article is an accidental duplication of an article that has already been published in Comparative Biochemistry and Physiology Part B: Biochemistry and Molecular Biology, Volume 255, 2021, 110593, https://doi.org/10.1016/j.cbpb.2021.110593. The duplicate article has therefore been withdrawn. The full Elsevier Policy on Article Withdrawal can be found at https://www.elsevier.com/about/our-business/policies/article-withdrawal.The Publisher regrets that this article is an accidental duplication of an article that has already been published in Comparative Biochemistry and Physiology Part B: Biochemistry and Molecular Biology, Volume 255, 2021, 110593, https://doi.org/10.1016/j.cbpb.2021.110593. The duplicate article has therefore been withdrawn. The full Elsevier Policy on Article Withdrawal can be found at https://www.elsevier.com/about/our-business/policies/article-withdrawal.